Analisis Spasial Faktor Lingkungan Kejadian Leptospirosis Di Kabupaten Boyolali Tahun 2015 - Yuniasy ari, Yuliadita Mega; , Sri Darnoto, SKM, MPH; , Miftahul Arozaq ,S.Si (2016)
Leptospirosis is a worldwide health problem, especially in the tropical and sub tropical and has a high rainfall. Leptospirosis is Leptospirosis caused by bacteria leptospira. Leptospirosis in Boyolali in 2012 is a remarkable event one contributing factor is environmental factors. The aim of this research is to know the spread of leptospirosis in Boyolali in 2015 and the environmental factors are dominant occurrences of the leptospirosis. The research method used observational, design by cross sectional approach. The population of this study is all patients leptospirosis as many as 19 peoples. In accordance with the inclusion and exclusion criteria sample of 12 peoples. The result of this research showed that the environmental factors are dominant with the existence of the garbage around the house, the distance of waste is about <500 meters, the existence of rats around the house, the job relating to the water and land, an open sewage system, and there is no trach camp.